Analisis Pengaruh Penyimpanan terhadap Kadar Vitamin C pada Cabai Rawit (Capsicum frutuscens L) dan Cabai Merah Besar (Capsicum annum L) dengan Metode Spektrofotometri - Rezqi Handayani; Nurul Qamariah; Tri Agung Rizky (Jurnal Surya Medika (JSM), 2020)
Chili is one of the fruits that contain vitamin C in a very large number. Vitamin C is one of the vitamins that is needed but cannot be synthesized in the body and has free radical antidote properties which will slow down the oxidation process that occurs in the body. One of the characteristics of vitamin C is a compound that is very easily oxidized due to the influence of heat, metal, and light so that in storage it needs special treatment to keep the levels low. One of the habits of the people in storing chili is in cold temperatures. This way trusted to maintain the condition of chili to always be fresh. But it is not yet known whether these conditions can guarantee vitamin C levels in them. Theoretically, the optimal storage for chili is at low temperatures between 2-15o C with humidity of 90-95% so that the chili remains fresh for ± 20 days. This research is to find out whether or not there is an influence between storage time on vitamin C levels in cayenne pepper and red. The research method used was quantitative analysis by measuring vitamin C levels in chili using a spectrophotometric instrument. The storage day indicator used in this study is the first, second, fourth and sixth day and the temperature used is 4oC. The results of the study for vitamin C levels in fresh cayenne pepper were 88.19 ± 1.39 mg/g, at two days storage was 82.04 ± 1.34 mg/g, at four days storage was 78.43 ± 1.02 mg/g and at six days storage was 78.17 ± 2.05 mg/g. The results of the study for vitamin C levels in fresh red chili were 81.54 ± 0.51 mg/g, at two days storage was 74.39 ± 0.89 mg/g, at four days storage was 42.49 ± 0.77 mg/g and at six days storage was 42.83 ± 0.17 mg/g. Based on research that has been done on cayenne pepper and large red chili it can be concluded, that with 4oC temperature in storage for 2 days, 4 days and 6 days in the refrigerator the levels of vitamin C are not well maintained.